(untitled) (Proceedings of the International Conference on Public Health, 2022)
A sedentary lifestyle is sufficient to cause muscle loss, insulin resistance, decreased aerobic capacity, and fat deposition. Regular physical activity and a proper diet are highly recommended for maintaining muscle strength, preventing nerve damage, lowering insulin resistance, and improving your quality of lifestyle. When you are inactive, there are changes in your body’s ability to regulate hormones and blood sugar levels. Participants came from worldwide to participate in the 12-week course of online lectures taught by a U.S.-based mentor. This paper uses the case study or field experience methodology. The course was modeled after a 12-week SAT prep course taught by an American professor to students in the United States, Tunisia, Hungary, India, Pakistan, Nepal, and Malaysia. This paper explores the factors that issue the students of the online learning experience. This is a case study in which the success factors are analyzed from both the instructor’s and the student’s perspectives. Student feedback on sitting posture, prolonged screen time, and mental effects has been evaluated to investigate the factors affecting student experience. At the same time, the success factors that contribute to the instructor’s experience have been assessed based on the effectiveness of the teaching platform, the extent of facilitation by the platform to personalize education to cater to individual student needs, and their comfort. While previous research has relied heavily on the specific issue between student satisfaction and their involvement, this study generates insights into all the healthrelated elements contributing to online learning success. The preliminary findings indicate what could be considered non-mainstream factors for success, such as the importance of posture, knowledge of ergonomics, break between the class, regulation of water intake, and spending time with family. This study also recognizes that further broader studies will be required to assess the external existence of the result and shows that individuals are not aware of prolonged screen time and the importance of taking a break. There is need of more research to improve it.